Outbreak of community-acquired Staphylococcus aureus skin infections in an Australian professional football team. Issue 6 (June 2021) - Shaban, Ramon Z.; Li, Cecilia; O'Sullivan, Matthew V.N.; Kok, Jen; Dempsey, Kathy; Ramsperger, Marc; Brown, Mitchell; Nahidi, Shizar; Sotomayor-Castillo, Cristina
Abstract: Objectives: Skin and soft tissue infections commonly affect athletes and can lead to cluster outbreaks if not managed appropriately. We report the findings of an investigation into an outbreak of community-acquired Staphylococcus aureus infection in an Australian professional football team. Design: Retrospective cross-sectional study. Methods: Nose, axilla, groin and throat swab were collected from 47 participants. MRSA and MSSA isolates underwent antibiotic susceptibility testing, binary typing and whole genome sequencing. Infection control practitioners (ICPs) investigated the training grounds for risk factors in the transmission of S. aureus . Results: Almost half of the participants (n = 23, 48.9%) were found to be colonised with MSSA. An outbreak cluster of MRSA ST5 closely related to the fusidic acid-resistant New Zealand NZAK3 clone was identified in a group of four players. MSSA ST15 and MSSA ST291 strains were found to have colonised and spread between two and five players, respectively. All participants were advised to undergo decolonisation treatment consisting of 4% chlorhexidine body wash and mupirocin nasal ointment for ten days. The ICP team identified several unhygienic practices within the club's shared facilities that may have played a role in the transmission of S. aureus . Conclusions: We report for the first time a community-associated S. aureus outbreak involving the highly successful fusidic acid-resistant MRSA ST5 clone in a professional football club associated with inadequate hygiene procedures. Management and prevention of S. aureus relies heavily on hygiene education and adherence to personal and environmental hygiene practices and policies.